The relative importance of morphological, physical and skill requirements for selecting talented U13 football players - Haroune, Dif; Ali, Bengoua; Chachou, Seddaoui (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to identify the key morphological (anthropometric) measurements, physical characteristics, and skills necessary for selecting young football players in the under-13 age group who have the potential for future excellence. We used a descriptive approach with a survey method, sampling 38 experts in sports training and measurement, focusing on football in the Arab world. A questionnaire with personal information and 37 relevant statements was employed for data collection, analyzed using SPSS. The study results revealed that for morphological requirements, body mass index (BMI) had the highest rating (M = 4.447; SD = 0.601). Among physical requirements, agility scored highest (M = 4.884; SD = 0.619). For skill requirements, ball control had the highest score (M = 4.763; SD = 0.489), followed by dribbling (M = 4.736; SD = 0.554), highlighting their importance for U-13 football players. The study identified several key requirements as highly important for selecting U-13 football players: for morphology, BMI, body fat percentage, body weight, and height; for physical abilities, agility, coordination, explosive power, strength, speed, flexibility, endurance, and motor speed; and for skills, ball control, dribbling, shooting accuracy, ball retention, and passing.